Impact of South African migration policies on the migrants’ quality of life and the role of social work - Masilo, Daniel Tuelo; Makhubele, Jabulani Calvin; Rabotata, Enoch; Mabasa, Allan; Matlakala, Frans Koketso; Mafa, Prudence; Baloyi, Themba; Kwakwa, Motshidisi (Technium Social Sciences Journal, 2021)
This paper discusses the impact of South African migration policies on the migrants’ quality of life. It does that with a particular focus on the Bill of Rights as contained in the Constitution of the Republic of South Africa. This is followed by a discussion on the role of social work in addressing any shortcomings that arise as a result of the implementation of the migration policies. This paper is primarily a desk study involving rigorous literature review on migration and relevant South African policies and international instruments. Theoretically, the ecosystems perspective is adopted to support and guide discussions in this paper. The discussions in this paper reveal that the South African migration policies do contribute towards the quality of life of the migrants, however, the challenges emanate from the implementation stage. It is from this understanding that various social work roles are discussed in order to help address the identified challenges.